2007
DOI: 10.1149/1.2761834
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of CoWP Film

Abstract: Electrochemical characterization of electrodeposition of CoWP films on copper substrate from a citrate electrolyte was carried out using voltammetry and chronoamperometry techniques. The voltammetry experiments revealed that codeposition of cobalt, tungsten, and phosphorus from an electrolyte containing cobalt sulfate, sodium tungstate, sodium hypophosphite, and tri-sodium citrate occurred via a nucleation process under mass-transfer control. The chronoamperometric study showed an instantaneous nucleation mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Peaks develop at a potential of -1.14 V in the case of hypophosphite containing electrolytes and the evolution of hydrogen occurs at -1.17 V. Therefore, it can be expected that there will be little or no hydrogen evolution if CoWP films are deposited at a potential more positive than -1.17 V. The polarisation curves of the cobalt, and the cobalt and tungstate containing electrolytes do not show a peak or plateau to indicate a limiting current. It has recently been reported that linear sweep voltammetry at various scan rates suggests that the induced codeposition of cobalt, tungsten and phosphorus from an electrolyte containing cobalt sulphate, sodium tungstate, sodium hypophosphite and tri-sodium citrate occurs via a nucleation process under mass transfer control [23]. Figure 1 also shows that dissolution of the deposits starts at around -0.8 V on the reverse scan when the electrolytes contain cobalt, and cobalt and hypophosphite ions.…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations
“…Peaks develop at a potential of -1.14 V in the case of hypophosphite containing electrolytes and the evolution of hydrogen occurs at -1.17 V. Therefore, it can be expected that there will be little or no hydrogen evolution if CoWP films are deposited at a potential more positive than -1.17 V. The polarisation curves of the cobalt, and the cobalt and tungstate containing electrolytes do not show a peak or plateau to indicate a limiting current. It has recently been reported that linear sweep voltammetry at various scan rates suggests that the induced codeposition of cobalt, tungsten and phosphorus from an electrolyte containing cobalt sulphate, sodium tungstate, sodium hypophosphite and tri-sodium citrate occurs via a nucleation process under mass transfer control [23]. Figure 1 also shows that dissolution of the deposits starts at around -0.8 V on the reverse scan when the electrolytes contain cobalt, and cobalt and hypophosphite ions.…”
Section: Methodsmentioning
confidence: 78%
“…A potentiostatic technique was preferred because it was found previously that the surface quality of the deposit plated by this method was better than that of a surface plated under galvanostatic conditions [23]. CoSO 4 Á7H 2 O, Na 2 WO 4 Á2H 2 O and NaH 2 PO 2 ÁH 2 O were used as the sources of cobalt, tungsten and phosphorus, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various metallic films have been proposed as capping/barrier layers, including NiReP [7], CoWP [8][9][10][11][12][13], CoWB [14], NiWB [15], NiCoP [16], CoMoP [17], and so on. These films were formed by using wet chemical methods such as electroless and electro plating.…”
Section: Introductionmentioning
confidence: 99%